2002
DOI: 10.1081/pfc-120015438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Inorganic and Organic Compounds on Sorption of 2,4-D and Atrazine

Abstract: In this study, the effects of size of adsorbent, temperature, pH of solution, ionic strength, presence of inorganic substances such as calcium ion, magnesium ions, chloride ions, fertilizers and presence of organic substances such as dissolved organic matter, surfactant, other herbicides on sorption of 2,4-D and atrazine onto rubber granules were investigated. The removal efficiency was more for fine adsorbent particles. Temperature played an important role in sorption process. Temperature effect was endotherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Both the positive relation of SOC and negative relation of soil pH with 2,4‐D sorption have been demonstrated previously for laboratory and field measurements (Bekbölet et al, 1999; Farenhorst et al, 2001; Alam et al, 2002; Spadotto and Hornsby, 2003). The soils in Alberta generally demonstrated larger Kd values than those previously documented for 2,4‐D in agricultural soils (Mallawatantri and Mulla, 1992; Bekbölet et al, 1999; Farenhorst et al, 2001; Gaultier et al, 2006), with the exception of soils from the MG ecoregion that had low sorption capacity.…”
Section: Discussionsupporting
confidence: 72%
“…Both the positive relation of SOC and negative relation of soil pH with 2,4‐D sorption have been demonstrated previously for laboratory and field measurements (Bekbölet et al, 1999; Farenhorst et al, 2001; Alam et al, 2002; Spadotto and Hornsby, 2003). The soils in Alberta generally demonstrated larger Kd values than those previously documented for 2,4‐D in agricultural soils (Mallawatantri and Mulla, 1992; Bekbölet et al, 1999; Farenhorst et al, 2001; Gaultier et al, 2006), with the exception of soils from the MG ecoregion that had low sorption capacity.…”
Section: Discussionsupporting
confidence: 72%
“…Standard methods [15] were adopted for the analysis of various water quality parameters. Gas Chromatograph (GC; GC-14A, Shimadzu, Japan) was used for the measurement of both 2,4-D and atrazine.…”
Section: Methodsmentioning
confidence: 99%
“…For example, about 12 million gallon of 2,4-D and 2,4,5-T, which contained toxic dioxin, were used over 4.5 million acre of land during Vietnam War from 1962 to 1971. [11] In earlier articles, [12,13] authors used rubber granules for removal of 2,4-D and atrazine from water environment, while the study outlined in another article [15] tried to quantify the impacts of commonly occurring inorganic and organic constituents in natural water on the sorption efficiency of rubber granules. In the present article, an attempt has been made to provide some information about the kinetic and equilibrium process that regulate the retention by the rubber granules of 2,4-D and atrazine from an aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, when compared with other lowcost adsorbents, GTR was among those with the best solute removal efficiencies (Alam et al 2000;Purakayastha et al 2003;Hatzinger et al 2004). Some of the organic compounds tested for adsorption by GTR have been anionic surfactants (Purakayastha et al 2005a, b), herbicides (2,4-D and atrazine; Alam et al 2000Alam et al , 2002Alam et al , 2005, and different alkanes and solvents (Rangarajan et al 1999). Removal of cadmium (III) from aqueous solution has also been achieved with GTR, and it was shown that the use of ultrasound increased the adsorption capacity (Entezari et al 2006).…”
Section: Introductionmentioning
confidence: 99%